Ancient and modern knowledges Transmission of models and techniques in the artistic and handicraft products in Sardinia through the centuries - Martorelli, Rossana (Saggi di Archeologia e Antichistica, 2022)
This volume contains the Proceedings of the Conference held on Oct. 7-8, 2022, at the Department of Humanities, Languages and Cultural Heritage of the University of Cagliari, as a conclusion of a two-year Research Project. The idea of dedicating a Research Project to artistic-craft production arose from years of fieldwork in both archaeological and art-historical disciplines, which have increasingly highlighted how much the long tradition of craftsmanship of which Sardinia is proud, which is expressed in artifacts made of ceramics, glass, metal, stone, wood and fabric, even at first glance reveals a transmission of technical and artistic 'knowledge' that is kept alive through the centuries.